Flow duration curve for evaluating ecosystem flow regulating functions in the Zambezi River Basin [Africa]. - Xueliang Cai; McCartney, Matthew P.; Smakhtin, Vladimir U. (2012)
Wetlands and forests have strong effects on hydrological processes by changing the rate of evaporation, transpiration, and flow routing in a basin, which affects basin water management such as dam operations. This study aims to assess the flow regulating functions of wetlands and forests using a flow duration curve (FDC) approach. We firstly identify wetlands and forests which are gauged both upstream and downstream. Reference conditions were then established using nearby sub-watersheds that contain few/no wetlands/forests. By transferring reference flows to the target sites and comparing the FDCs for with and without wetland/forest conditions we then assess the hydrological impacts on flood attenuation and base flow maintenance. Results of a floodplain wetland suggest that it decrease flood flows and increase low flows. The extent of this function could be quantified which gives useful indications for water resources planning and management.